Truth, reparation and social justice: victims’ and academic perspectives on the harms caused by asbestos companies - Buggenhout, Marijke Van (Criminological encounters, 2022)
This short piece stems from personal experience about the environmental harm caused by one of the biggest former asbestos facilities, Eternit, located in the small Belgian rural village of Kapelleop-den-Bos. Combined with an academic perspective, this piece highlights the relevance of environmental restorative justice in addressing the violations and harms experienced by asbestos victims.It brings to light the struggles of victim associations to challenge the power, and complete lack of accountability of (former) asbestos producing companies worldwide and offers an understanding of strategies used to promote immunity to the powerful.